Inclusion of whey in the diet of fattening rams - Ninahuanca Carhuas, Jordan (2023)
The effect of including whey in the diet of rams in the fattening stage of the company SAIS Pachacutec S.A.C, located in the central mountains of Peru at an altitude of 4119 m was evaluated. In total, 120 five-month-old Corriedale male rams from the “Cabaña” (n=40), “Plantel” (n=40) and “Majada” (n=40) genetic sections were used. Rams from each section was randomly distributed into four treatment groups (n=10 per group): T1 (0%, control); T2 (15%); T3 (25%) and T4 (35% whey). The whey was added to the concentrate (bran feed). The study included 14 days of adaptation to the feed and 90 days of trial. Final weight, weight gain and carcass weight were significantly different between treatments and sections (p<0.05), being greater in T4 and in the Cabaña section (final weight: 48.7 ± 0.6 kg; weight gain: 379.4 g/day; carcass weight: 20.9 ± 1.2 kg). Carcass yield was similar between groups (43.0 ± 0.01%; p>0.05). The results suggest that, with a greater amount of whey, within of the quantities used in the study, better fattening performances of rams are obtained.